Effect of CO2 Flow Rate on the Synthesis of Sliced Activated Carbon from Date Palm Tree Fronds (Agro Waste) by Physical Activation - Shoaib, Muhammad; M. Al-Swaidan*, Hassan (Asian Journal of Chemistry, 2014)
Among all the date producing countries, Saudi Arabia produced around 15 % of the total production around the world. During the pruning process of date palm trees, fronds are considered as a agro waste material. Due to the voluminous availability, the date palm fronds are considered as a starting material for activated carbon (AC) production. The BET surface areas of the activated carbons prepared at a CO2 flow rate of 25, 50, 100, 150, 200 and 250 mL/min after 0.5 h activation time are 610,1094, 854, 877, 866 and 886 m2/g, respectively. The activated carbon prepared at a flow rate of 50 mL/min attains larger surface area 1094 m2/g. Effect of CO2 flow rate on the synthesis strongly affects the BET surface area and pore volume, they both increases at a flow rate from 25 to 50 mL/min from 25 to 50 mL/min, whereas a constant behaviour were observed at a flow rate of CO2 from 100 to 250 mL/min. Moreover by increasing the CO2 flow rate the yield decreases linearly from 23.25 to 14.70 %.